Enhancement of Cu+ stability under a reducing atmosphere by the long-range electromagnetic effect of Au. Issue 36 (2nd September 2022) - Huang, Xin; Li, Haitao; Zhang, Yin; Wu, Ruifang; Ban, Lijun; Xi, Lin; Yin, Zhifang; Peng, Jian; Zhao, Yongxiang; Fang, Li
Abstract : In conventional thermocatalytic reactions under a reducing atmosphere, stabilization of the active Cu + component and inhibition of over-reduction into metallic Cu 0 are extremely challenging. Abstract : In conventional thermocatalytic reactions under a reducing atmosphere, stabilization of the active Cu + component and inhibition of over-reduction into metallic Cu 0 are extremely challenging. In this study, Au@Cu2 O core–shell nano-catalysts with different Cu2 O shell thicknesses were synthesized, and the effect of the Au nano-core on Cu + stability under a reducing atmosphere and the catalytic performance of Cu + in the ethynylation of formaldehyde were investigated. The Au nano-core facilitates Cu2 O dispersion and leads to an increase of 0.2–0.5 eV in electron binding energies of Cu2 O and Cu2 C2 in the range of 27–55 nm, attributed to the long-range electromagnetic effect of Au NPs. Specifically, active Cu + centers exhibit high stability under a reducing atmosphere due to the long-range electromagnetic effect of the Au nano-core. In the ethynylation of formaldehyde as a probe reaction, Cu + /(Cu 0 + Cu + ) on Au@Cu2 O catalysts remained at 88–91%. The catalytic performance in the ethynylation of formaldehyde revealed that the introduction of an Au nano-core into Cu-based catalysts increased the TOF from 0.37 to 0.7 h −1, and decreased the activation energy from 42.6 to 38.1 kJ mol −1 . Additionally, the Cu + /(Cu 0 + Cu + ) ratios and the catalytic performance in the ethynylation of formaldehyde (BD yield = 65%, BD selectivity = 95%) on Au@Cu2 O catalysts remained constant after nine cycles, while pure Cu2 O readily deactivated due to the dramatically reduced Cu + /(Cu 0 + Cu + ) ratios and carbyne deposition. In summary, Cu + in Cu-based catalysts showed high catalytic activity and stability during the ethynylation of formaldehyde due to the long-range electromagnetic effect of the Au nano-core.